The Police-Prosecution Nexus in Pakistan: Exploring Institutional Coordination and its Impact on Criminal Justice Outcomes - Ali, Syed Hyder; Rehman, Tansif Ur (Regional Lens, 2025)
In Pakistan, the criminal justice system is largely influenced by the close relationship between the police and the prosecution. Ineffective coordination has been experienced over the years due to overlapping mandates, lack of resources, and institutional rivalries. Such fragmentation tends to impair the proceedings of cases, corrosion of trial results, and depletion of public trust. Findings show that informal "shadow" networks can speed up evidence transfer but also spread inconsistencies in evidentiary standards. The study supposes that by increasing institutional synergies, i.e., common protocols, common training programs, and performance-based rewards, case-dismissal rates may be reduced drastically, trial times may be shorter, and public confidence may be enhanced. These are needed since a justice system that is grappling with systemic inertia requires them.